2019
DOI: 10.1017/rdc.2019.98
|View full text |Cite
|
Sign up to set email alerts
|

The 1953–1965 rise in Atmospheric bomb 14C in Central Norway

Abstract: Sub-annual measurements, eight increments per year, of cellulose in a Scots pine tree growing in central Norway are presented as a proxy for tropospheric 14CO2 at biweekly to monthly resolution. The results are validated by comparison to direct atmospheric measurements in the years 1959–1965, and a new dataset is obtained for 1953–1958. In this period, our cellulose measurements deviate from the Bomb 13 NH1 calibration curve, which is derived from single-year measurements of tree rings. This is due to seasonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
(1 reference statement)
3
5
0
Order By: Relevance
“…Stuiver and Braziunas (1998) found only a minimal Δ 14 C offset (-0.3 ± 0.7 ‰) for AD 1615-1715 but an offset of 26 ± 6 14 C yr younger for AD 1545-1615 for a Siberian larch tree (67°N, 123°E) compared to a tree from Washington state (48°N, 124°W) which is in good agreement with Büntgen et al (2018). Data from northern Norway from trees growing during the peak of nuclear weapons testing also had higher 14 C (Hua and Barbetti 2007;Svarva et al 2019) but may not be representative of natural offsets due to the high latitude of many of the atmospheric bomb tests. Büntgen et al (2018) reported elevated 14 C values for some trees growing above 60ºN at the peak of the AD 774/5 Miyake event (Miyake et al 2012).…”
Section: Intcal20 14 C Calibration Curve 729supporting
confidence: 63%
“…Stuiver and Braziunas (1998) found only a minimal Δ 14 C offset (-0.3 ± 0.7 ‰) for AD 1615-1715 but an offset of 26 ± 6 14 C yr younger for AD 1545-1615 for a Siberian larch tree (67°N, 123°E) compared to a tree from Washington state (48°N, 124°W) which is in good agreement with Büntgen et al (2018). Data from northern Norway from trees growing during the peak of nuclear weapons testing also had higher 14 C (Hua and Barbetti 2007;Svarva et al 2019) but may not be representative of natural offsets due to the high latitude of many of the atmospheric bomb tests. Büntgen et al (2018) reported elevated 14 C values for some trees growing above 60ºN at the peak of the AD 774/5 Miyake event (Miyake et al 2012).…”
Section: Intcal20 14 C Calibration Curve 729supporting
confidence: 63%
“…Nuclear test activity resumed in the second half of 1961, causing increased atmospheric 14 C activity, as seen in the 1962 spring/early summer biomass 14 C concentration. Evolution and 14 C concentrations in seeds compare reasonably well to the Trondheim pine tree-ring tissues of the same period (Svarva et al 2019: see also Figure S1).…”
Section: Resultssupporting
confidence: 61%
“…Growth seasons of different tree-ring species in different regions employed in our compilation are not identical, but they are similar (e.g., Hua et al 2012;Cain et al 2018;Turney et al 2018;Svarva et al 2019;Ancapichún et al 2021). The duration of growing seasons can also vary slightly from one year to another.…”
Section: Timing Of Tree-ring Growth Seasonsmentioning
confidence: 99%
“…For the sub-annual Norwegian tree-ring record (8 incremental samples per year) of Svarva et al (2019), the first and last increments of each annual tree ring were excluded from our analyses. This is because of the possibility of cross-ring-boundary sampling resulting in unreliable Δ 14 C values, especially for the bomb peak period (Svarva et al 2019).…”
Section: Tree Ringsmentioning
confidence: 99%
See 1 more Smart Citation